Observation of the open-charm tetraquark candidate T*cs0 (2870)0 in the B-→D-D0K0S decay - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review letters, 2025)
An amplitude analysis of 𝐵−→𝐷−⁢𝐷0⁢𝐾0𝑆 decays is performed using proton-proton collision data, corresponding to an integrated luminosity of 9 fb−1, collected with the LHCb detector at center-of-mass energies of 7, 8, and 13 TeV. A resonant structure of spin-parity 0+ is observed in the 𝐷0⁢𝐾0𝑆 invariant-mass spectrum with a significance of 5.3⁢𝜎. The mass and width of the state, modeled with a Breit-Wigner line shape, are determined to be 2883±11±8 MeV/𝑐2 and 87+22−47 ±17 MeV, respectively, where the first uncertainties are statistical and the second systematic. These properties and the quark content are consistent with those of the open-charm tetraquark candidate 𝑇*𝑐⁢𝑠⁢0⁢(2870)0 observed previously in the 𝐷+⁢𝐾− final state of the 𝐵−→𝐷−⁢𝐷+⁢𝐾− decay. This result confirms the existence of the 𝑇*𝑐⁢𝑠⁢0⁢(2870)0 state in a new decay mode. The 𝑇*𝑐⁢𝑠⁢1⁢(2900)0 state, reported in the 𝐵−→𝐷−⁢𝐷+⁢𝐾− decay, is also searched for in the 𝐷0⁢𝐾0𝑆 invariant-mass spectrum of the 𝐵− →𝐷−⁢𝐷0⁢𝐾0𝑆 decay, without finding evidence for it.